ASSESSMENT OF PHYSICO-CHEMICAL PARAMETERS OF SOILS IN ZOOTECHNICAL FARMS AREA FROM TICHILEȘTI AND TUFEȘTI LOCALITIES (BRĂILA COUNTY) - GHIORGHIU, Eduard-Gabriel; GLIGOR, Delia; BĂLC, Ramona (Studia Universitatis Babeș-Bolyai Ambientum, 2017)
Two growing-fattening pig farms – non-organic and organic - have been chosen in order to estimate the potential environmental impacts of heavy pig production. The above mentioned farms are situated in Tichilești-Tufești area, Brăila County, Romania. This area is situated in the north-eastern part of the Romanian Plain, which is delimitated by the Danube River in the southern part. Is one of the highest agricultural potential areas, reflected in a development of the economical sector based on zootechnical farms. Using the electrochemical methods, the nitrites and sulphides, from soil and water, together with physico-chemical parameters have been analyzed. The obtained results indicate the presence of the above mentioned chemical compounds in a small amount, excepting one location, situated near the organic farm. The maximum permissible limits imposed by the Romanian legislation are exceeded only for drinking water, being in normal values for all analyzed soil samples. In addition, a positive correlation between clay and nitrite/sulphides content can be observed.